Importance of contact lens power and thickness in oxygen transmissibility - Lira, Madalena (2015)
PURPOSE: The aim of this work was to study the central and peripheral thickness of several contact lenses (CL) with different powers and analyze how thickness variation affects CL oxygen transmissibility. METHODS: Four daily disposable and five monthly or biweekly CL were studied. The powers of each CL were: the maximum negative power of each brand; -6.00 D; -3.00 D; zero power (-0.25 D or -0.50 D), +3.00 D and +6.00 D. Central and peripheral thicknesses were measured with an electronic thickness gauge. Each lens was measured five times (central and 3mm paracentral) and the mean value was considered. Using the values of oxygen permeability given by the manufacturers and the measured thicknesses, the variation of oxygen transmissibility with lens power was determined. RESULTS: For monthly or biweekly lenses, central thickness changed between 0.061 ± 0.002 mm and 0.243 ± 0.002 mm, and peripheral thickness varied between 0.084 ± 0.002 mm and 0.231 ± 0.015 mm. Daily disposable lenses showed central values ranging between 0.056 ± 0.0016 mm and 0.205 ± 0.002 mm and peripheral values between 0.108 ± 0.05 and 0.232 ± 0.011 mm. Oxygen transmissibility (in units) of monthly or biweekly CL ranged between 39.4 ± 0.3 and 246.0 ± 14.4 and for daily disposable lenses the values range between 9.5 ± 0.5 and 178.1 ± 5.1. CONCLUSIONS: The central and peripheral thicknesses change significantly when considering the CL power and this has a significant impact on the oxygen transmissibility. Eyecare practitioners must have this fact in account when high power plus or minus lenses are fitted or when continuous wear is considered.